Primary School Teacher’s Perceptions of the Principal’s Role in the Development of their Motivation, Professional Empowerment and Satisfaction - Καράμπελα, Χρυσούλα; Αλεξανδρόπουλος, Γεώργιος (Education Sciences, 2022)
The purpose of this research is to investigate views of 164 primary school teachers, who served in Laconia regional unity primary schools on the principal’s role in the development of motivating factors, professional satisfaction and empowerment. At the same time, investigate the effect of the demographic - professional characteristics of the educators on these perceptions. The results indicated that the teachers are generally satisfied with the actions and attitudes of the principal that contribute to motivation, professional satisfaction and empowerment. As for the dimensions of empowerment, dominant was autonomy, for teaching and classroom issues, professional growth and self-effectiveness. Next come professional development and participation in decision making. The gender and the academic qualifications of the educators do not differentiate any of the variables studied. On the contrary, the age is an important factor in differentiating teacher’s perceptions of the principal's actions to motivate and job satisfaction, while working relationship, age and previous experience affect all the variables of empowerment and its individual dimensions.